SISTEM INFORMASI REPOSITORI SKRIPSI BERBASIS WEB PADA STMIK SYAIKH ZAINUDDIN NW ANJANI - Muh. Fahrurrozi; Khairunnazri; Lalu Puji Indra Kharisma (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
This Repository Information System is an idea that appears to help agencies manage thesis archiving that was previously still done conventionally by collecting the results of thesis binding (hardcopy) and CD containing the sis files along with the source code of the program that was made (softcopy) into a digital system new and modern. Repository Information System is a system that is expected to help the School of Information and Computer Management (STMIK) Shaykh Zainuddin NW Anjani to organize the archiving of thesis data that has been done by students to be neater, safer and easier to manage. The repository information system was developed using the waterfall software development process model and object oriented analysis modeling, then implemented using the Codeigniter programming language, one of the PHP frameworks. The result of this study is a website-based the sis repository system that can archive student thesis data and can also be used to search and display existing the sis data through the admin or user interface in this case students.